ASSESSING HEALTHCARE SERVICE QUALITY THROUGH IMPORTANCE PERFORMANCE ANALYSIS: A PATIENT PERCEPTION STUDY AT MEGA BUANA HOSPITAL PALOPO - Faradiba Anggraeni; Muhammad Azwar; Arlin Adam; Syamsul Bahri; Lilis Widiastuty; Mohamad Husni Thamrin (Universitas Islam Negeri Alauddin Makassar, 2025)
Background: Service quality is a key determinant of patient satisfaction and hospital performance. Understanding the gap between patient expectations and perceptions is essential for strengthening healthcare delivery. Objective: This study aimed to assess healthcare service quality at Mega Buana Hospital Palopo, Indonesia, using SERVQUAL dimensions and to analyze their influence on patient satisfaction. Method: A cross sectional survey was carried out from July to August 2025 with 143 patients recruited through accidental sampling. Data were collected using the SERVQUAL questionnaire comprising 22 indicators across five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Descriptive statistics were applied to evaluate gaps between expectations and perceptions, while multiple regression analysis tested the effect of each dimension on patient satisfaction. Results: The findings revealed negative gaps across all dimensions, suggesting that perceived services did not meet expectations. The largest gap was observed in reliability (–0.58), followed by tangibles (–0.40), empathy (–0.33), responsiveness (–0.29), and assurance (–0.22). Regression results showed that responsiveness (β = 0.34, p = 0.002) and tangibles (β = 0.29, p = 0.011) significantly predicted patient satisfaction, while reliability, assurance, and empathy were not significant. The model explained 58% of the variance in patient satisfaction (R² = 0.58, F = 24.31, p < 0.001). Conclusion: Service quality at Mega Buana Hospital Palopo needs improvement, especially in reliability. Enhancing responsiveness and tangible aspects such as promptness, communication, and facility conditions will be critical to improve patient satisfaction and hospital performance.